2021
DOI: 10.1007/s11356-021-15561-3
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of treated wastewater and non-potable groundwater in the manufacture of concrete: major challenge of environmental preservation

Abstract: This work concerns the reuse of treated wastewater from Er-Rachidia wastewater treatment plant (WWTP) in the mixing of ordinary B25 concrete, in order to reduce the overexploitation of groundwater, avoid its discharge into watercourses and reduce the risk of environmental pollution due to its mineral and organic matter load. In this respect, Tree types of mixing water were used in this study: Drinking Water (DW), Groundwater (GW) and Treated Wastewater (TW). The results recorded for each type of mixing water, … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(31 citation statements)
references
References 30 publications
(3 reference statements)
0
29
0
2
Order By: Relevance
“…Abushanab and Alnahhal (2021) used a combination of treated sewage, calcium nitrite, fly ash, and superplasticizer to manufacture concrete samples and it was mentioned that wastewater concrete had markedly higher permeability than that of control samples 68 . Bouaich et al (2022) 69 and Tanli et al (2022) 71 also reported similar results. They indicated that using domestic wastewater with or without recycled plastic could reduce the density of concrete.…”
Section: The Effect Of Domestic and Industrial Wastewater On Concrete...mentioning
confidence: 89%
See 3 more Smart Citations
“…Abushanab and Alnahhal (2021) used a combination of treated sewage, calcium nitrite, fly ash, and superplasticizer to manufacture concrete samples and it was mentioned that wastewater concrete had markedly higher permeability than that of control samples 68 . Bouaich et al (2022) 69 and Tanli et al (2022) 71 also reported similar results. They indicated that using domestic wastewater with or without recycled plastic could reduce the density of concrete.…”
Section: The Effect Of Domestic and Industrial Wastewater On Concrete...mentioning
confidence: 89%
“…The standards report that pH must be ≥4, 32 ≥6, 43 >5, 35,36 and 6–9 38 . Although the U.S. Environmental Protection Agency reported the maximum amount of BOD 5 should be limited to 30 mg/L, several studies have used wastewater in higher amounts than this number 23,57–59,63,64,66,69 . Unfortunately, there is no standard regarding COD limitations.…”
Section: The Effect Of Domestic and Industrial Wastewater On Concrete...mentioning
confidence: 99%
See 2 more Smart Citations
“…This may be due to pore filling properties of TDS (Aldossary et al, 2020, Zervaki et al, 2013, Vaičiukynienė et al, 2021, which produced higher compressive strength at 3 and 7 days, but about 92% of control (de Matos et al, 2020), higher than control before three months old and similar to control thereafter (Gupta et al, 2020, Klus et al, 2019. Other properties such as workability, initial setting time were reduced but still within the acceptable limit, which may be due to the presence of Cl ion in TDS (Aldossary et al, 2020, Zervaki et al, 2013, Bouaich et al, 2021. However, untreated wash water is not recommended to be used as process water for concrete production due to the low workability and low compressive strength of the concrete produced (Ghrair et al, 2020).…”
Section: Introduction 11 Backgroundmentioning
confidence: 99%